Conductive film, solar cell, and organic el element
Patent Information
- Application Number
- JP2023103212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-09
AI Technical Summary
【0009】 本発明によれば、太陽電池または有機EL素子に適用した際の太陽電池の変換効率または有機EL素子の発光効率の経時変化が少ない導電性フィルムを提供できる。また、本発明によれば、変換効率の経時変化が少ない太陽電池、および、発光効率の経時変化が少ない有機EL素子を提供できる。
Smart Images

Figure 2025002844000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive film, a solar cell, and an organic EL device. [Background technology]
[0002] Conductive films having conductive thin wires (thin wire-like wiring exhibiting conductivity) are widely used for various applications such as touch panels, solar cells, and EL (electroluminescence) elements, etc. The conductive films are expected to be used as transparent electrodes provided in solar cells, EL elements, etc.
[0003] As a technique relating to a conductive film, for example, Patent Document 1 discloses a conductive film comprising a support, a metal mesh layer made of a conductive metal, and a binder amount of 0.2 g / m 2 The following techniques are disclosed relating to a conductive element having a layer containing conductive fine particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-138628 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors have studied conductive films having conductive thin metal wires with reference to Patent Document 1, and have found that there is room for further improvement in the change over time in the function of elements such as solar cells and organic EL elements when a conductive film produced with reference to the method described in the above document is applied to the elements.
[0006] In view of the above circumstances, an object of the present invention is to provide a conductive film that, when applied to a solar cell or an organic EL element, exhibits little change over time in the conversion efficiency of the solar cell or the luminous efficiency of the organic EL element.Another object of the present invention is to provide a solar cell with little change over time in conversion efficiency and an organic EL element with little change over time in luminous efficiency. [Means for solving the problem]
[0007] As a result of extensive research into the above problems, the present inventors have found that the above problems can be solved by the following configuration.
[0008] [1] A conductive film comprising a substrate, a metal layer composed of thin metal wires arranged on the substrate, and a transparent conductive layer arranged on the substrate between the thin metal wires, wherein the thin metal wires contain metal particles and a polymer compound different from gelatin, and the thin metal wires do not contain gelatin, or, if the thin metal wires contain gelatin, the gelatin content in the thin metal wires is 0.100 g / m 2 The conductive film is as follows: [2] The conductive film according to [1], wherein the polymer compound contains a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer. [3] The conductive film according to [1] or [2], wherein the transparent conductive layer contains fine particles of a conductive metal oxide and a binder. [4] The conductive film according to [3], wherein the binder is a resin containing a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer. [5] The conductive film according to [3] or [4], wherein the conductive metal oxide is tin oxide doped with antimony. [6] The conductive film according to any one of [1] to [5], wherein the transparent conductive layer contains a conductive polymer. [7] The conductive film according to [6], wherein the conductive polymer contains polyethylenedioxythiophene having polystyrenesulfonic acid as a counter ion. [8] The conductive film according to any one of [1] to [7], further comprising an undercoat layer disposed between the substrate and the metal layer, the undercoat layer containing a resin including a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer. [9] The conductive film according to any one of [1] to [8], wherein the thin metal wires have a line width of 1 to 4 μm.
[10] The conductive film according to any one of [1] to [9], which has a mesh pattern formed by the thin metal wires.
[11] The conductive film according to
[10] , wherein the mesh pattern has a rhombus shape.
[12] The conductive film according to any one of [1] to
[11] , wherein the substrate has a thickness of 30 to 50 μm.
[13] The conductive film according to any one of [1] to
[12] , wherein the transparent conductive layer is arranged in a pattern.
[14] A solar cell comprising the conductive film according to any one of [1] to
[13] .
[15] An organic EL device comprising the conductive film according to any one of [1] to
[13] . Effect of the Invention
[0009] According to the present invention, it is possible to provide a conductive film which, when applied to a solar cell or an organic EL element, exhibits little change over time in the conversion efficiency of the solar cell or the luminous efficiency of the organic EL element. Also, according to the present invention, it is possible to provide a solar cell having little change over time in conversion efficiency and an organic EL element having little change over time in luminous efficiency. [Brief description of the drawings]
[0010] [Figure 1]FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a conductive film of the present invention. [Diagram 2] FIG. 2 is a plan view showing an example of a mesh pattern formed by thin metal wires of the conductive film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The conductive film of the present invention will be described in detail below with reference to the drawings. The following description of the components is based on a representative embodiment of the present invention, and the present invention is not limited to such an embodiment. Also, the drawings shown below are illustrative for explaining the present invention, and the present invention is not limited by the drawings shown below. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In this specification, when two or more types of a component are present, the "content" of the component means the total content of those two or more components. In this specification, when a certain component "contains a certain substance as a main component," it means that the content of that substance is 50 mass% or more of the total mass of the component. Also, when a certain component "does not contain" a certain substance, it means that the content of that substance in the component is 0.1 mass% or less of the total mass of the component. In this specification, "g" and "mg" represent "g mass" and "mg mass", respectively. As used herein, an "organic group" refers to a group containing at least one carbon atom. In this specification, "(meth)acrylic" is a general term including acrylic and methacrylic, and means "at least one of acrylic and methacrylic". Similarly, "(meth)acrylate" means "at least one of acrylate and methacrylate".
[0012] In this specification, the term "polymer" or "polymer compound" refers to a compound having a weight-average molecular weight of 2000 or more. Here, the weight-average molecular weight is defined as a polystyrene-equivalent value measured under the following conditions using gel permeation chromatography (GPC). Equipment: Tosoh Corporation HLC-8320GPC Column: Tosoh Corporation TSK-GEL G3000PWXL Column temperature: 35℃ ·Flow rate: 0.5mL / min Calibration curve: Poly sodium acetate standard manufactured by Sowa Science Co., Ltd. Eluent: A mixture of sodium dihydrogen phosphate dodecahydrate / disodium hydrogen phosphate dihydrate (34.5g / 46.2g) diluted to 5000g with pure water.
[0013] In this specification, unless otherwise specified, "transparent" means that the transmittance at the main wavelength of the exposure wavelength is 30% or more. The transmittance is preferably 50% or more, more preferably 60% or more, even more preferably 80% or more, and particularly preferably 90% or more. The upper limit is often less than 100%. The transmittance is measured using a known transmittance measuring device (for example, the V-700 series manufactured by JASCO Corporation). In this specification, angles expressed by specific numerical values and angle-related expressions such as "parallel," "perpendicular," and "orthogonal" include error ranges generally accepted in the relevant technical field, unless otherwise specified. In this specification, the term "principal surface" refers to the surface having the largest area in a film-, sheet- or plate-like member.
[0014] [Conductive film] The conductive film of the present invention (hereinafter also referred to as "the conductive film") has a substrate, a metal layer composed of thin metal wires arranged on the substrate, and a transparent conductive layer arranged between the thin metal wires on the substrate. The thin metal wire contains metal particles and a polymer different from gelatin, and the thin metal wire does not contain gelatin, or, if the thin metal wire contains gelatin, the gelatin content in the thin metal wire is 0.100 g / m 2 The following is the result.
[0015] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a conductive film according to the present invention. The conductive film 10 shown in Fig. 1 is composed of a substrate 12, a metal layer 14, and a transparent conductive layer 18. The metal layer 14 is composed of thin metal wires 16, and is disposed on the surface 12a of the substrate 12. The transparent conductive layer 18 is formed so as to cover the surface 12a of the substrate 12 and the metal layer 14, and is thereby disposed between the thin metal wires 16 on the surface 12a. Although FIG. 1 shows three thin metal wires 16 extending in a direction perpendicular to the paper surface, the arrangement and number of the thin metal wires 16 are not particularly limited.
[0016] 〔substrate〕 The type of the substrate is not particularly limited as long as it is a member capable of supporting the metal layer and the transparent conductive layer. Examples of the substrate include a plastic substrate, a glass substrate, and a metal substrate, and a plastic substrate is preferred. The substrate is preferably a flexible substrate, since the conductive member obtained has excellent bendability and a flexible solar cell and organic EL element can be produced. Examples of the flexible substrate include the above-mentioned plastic substrate. The thickness of the substrate is not particularly limited, and is often 15 to 500 μm, preferably 25 to 120 μm, and more preferably 30 to 50 μm from the viewpoint of thinness and flexibility. If the substrate also serves other functions such as a touch surface in addition to its function as a substrate, it can be designed to have a thickness of more than 500 μm.
[0017] As materials constituting the substrate, resins with a melting point of about 290°C or less, such as polyethylene terephthalate (PET) (258°C), polycycloolefin (134°C), polycarbonate (250°C), acrylic film (128°C), polyethylene naphthalate (269°C), polyethylene (135°C), polypropylene (163°C), polystyrene (230°C), polyvinyl chloride (180°C), polyvinylidene chloride (212°C), and triacetyl cellulose (290°C), are preferred, with PET, polycycloolefin, or polycarbonate being more preferred. Among these, PET is particularly preferred as a flexible substrate due to its excellent adhesion to the metal thin wires. The numbers in parentheses above are melting points or glass transition temperatures.
[0018] The substrate is preferably transparent to the exposure wavelength. The total light transmittance of the substrate is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. The upper limit is not particularly limited and may be less than 100%. The total light transmittance of the substrate is measured using "Plastics - Determination of total light transmittance and total light reflectance" as specified in JIS (Japanese Industrial Standards) K 7375:2008.
[0019] A preferred embodiment of the substrate is a substrate that has been subjected to at least one treatment selected from the group consisting of atmospheric pressure plasma treatment, corona discharge treatment, and ultraviolet irradiation treatment. By performing the above treatment, hydrophilic groups such as OH groups are introduced onto the surface of the substrate, which further improves the adhesion of the metal layer.
[0020] Another preferred embodiment of the substrate is one in which an undercoat layer is disposed between the substrate and the metal layer. The undercoat layer preferably contains a polymer compound different from gelatin, and more preferably contains a resin containing a repeating unit derived from a styrene monomer and a repeating unit derived from a (meth)acrylate monomer. By forming this undercoat layer, the adhesion of the metal layer to the substrate is further improved. The preferred embodiment of the polymer compound different from gelatin contained in the undercoat layer is the same as the preferred embodiment of the specific polymer described below.
[0021] The method of forming the undercoat layer is not particularly limited, and for example, a method of applying a composition for forming an undercoat layer containing a polymer compound different from gelatin onto a substrate, and performing a curing treatment by heating and irradiating light as necessary can be mentioned. The composition for forming an undercoat layer may contain a solvent as necessary. The type of the solvent is not particularly limited, and examples include the solvents used in the composition for forming a photosensitive layer described later. In addition, as the composition for forming an undercoat layer containing a polymer compound different from gelatin, a latex containing particles of a specific polymer described later can be used. The thickness of the undercoat layer is not particularly limited, but is preferably 0.02 to 1.5 μm, and more preferably 0.05 to 1.0 μm, in terms of superior adhesion of the metal layer to the substrate.
[0022] [Metal layer] On the surface of the conductive film substrate, a metal layer made of metal particles and thin metal wires containing a polymer compound different from gelatin (hereinafter also referred to as a "specific polymer") is disposed.
[0023] The arrangement of the thin metal wires in the metal layer is not particularly limited. The metal layer may have a pattern formed by thin metal wires. The pattern is not particularly limited, and is preferably, for example, a triangle such as an equilateral triangle, an isosceles triangle, or a right-angled triangle; a quadrangle such as a square, a rectangle, a rhombus, a parallelogram, or a trapezoid; a (regular) n-gon such as a (regular) hexagon or a (regular) octagon; a circle, an ellipse, a star, or a geometric figure combining these figures, and more preferably, a mesh shape (mesh pattern). A random mesh pattern having a random shape may also be used.
[0024] FIG. 2 is a plan view showing an example of a mesh pattern formed by thin metal wires. The mesh shape refers to a shape including a plurality of openings 20 that are separated from each other by intersecting thin metal wires 16, as shown in FIG. 2. In FIG. 2, the openings 20 have a square shape with a side length of L, but the openings of the mesh pattern may have other shapes, for example, polygonal shapes (for example, triangles, quadrilaterals (diamonds, rectangles, etc.), hexagons, and random polygons). The shape of the sides may be curved shapes other than straight lines, or may be arc-shaped. In the case of arc-shaped shapes, for example, two opposing sides may be arc-shaped convex outward, and the other two opposing sides may be arc-shaped convex inward. The shape of each side may be a wavy line shape in which an outwardly convex arc and an inwardly convex arc are continuous. Of course, the shape of each side may be a sine curve. The shape of the mesh pattern formed by the thin metal wires 16 is preferably a square, a parallelogram, or a rhombus, and more preferably a rhombus.
[0025] The length L of one side of the opening 20 is preferably 1500 μm or less, more preferably 1300 μm or less, and even more preferably 1000 μm or less. The length L is preferably 5 μm or more, more preferably 30 μm or more, and even more preferably 80 μm or more. When the length of one side of the opening is within the above range, it is possible to further maintain good transparency. In particular, when the mesh pattern is rhombic, the length L is preferably 100 μm or more and 500 μm or less.
[0026] From the viewpoint of visible light transmittance, the opening ratio of the mesh pattern formed by the thin metal wires is preferably 90% or more, more preferably 95% or more, and even more preferably 99% or more. There is no particular upper limit, but it may be less than 100%. The aperture ratio means the ratio (area ratio) of the area occupied by the openings to the entire area occupied by the mesh pattern in the area of the conductive film where the mesh pattern is formed.
[0027] The thickness of the metal layer is not particularly limited, but is preferably 0.5 to 3.0 μm, and more preferably 0.8 to 1.5 μm. The thickness of the metal layer is determined by using a scanning electron microscope to arbitrarily select five locations corresponding to one thin metal wire and calculate the arithmetic average value of the thicknesses at the five locations.
[0028] <Thin metal wire> The thin metal wires are the portion that imparts conductive properties to the conductive film by containing metal particles. As the metal constituting the metal particles, a simple metal selected from the group consisting of silver (metallic silver), copper (metallic copper), gold (metallic gold), nickel (metallic nickel) and palladium (metallic palladium) and a mixture (alloy) of two or more metals selected from the above group are preferred in terms of superior conductive properties. Among these, it is more preferred that the metal particles contain silver, and further more preferred that they are composed of simple silver or a mixture (alloy) of silver and copper, and particularly preferred that they are composed of simple silver.
[0029] In this specification, the thin metal wires refer to thin wire-like regions that are disposed on the surface of a substrate and are integrally formed of a material containing metal. For example, the intermediate layer formed by the step H described below constitutes thin metal wires together with the thin wire-like metal-containing layer (silver-containing layer) formed by the steps A and B described below. In addition, the thin metal wires may or may not be electrically connected to an external member of the conductive film. A part of the thin metal wires may be a dummy electrode that is electrically insulated from the outside.
[0030] The average particle size of the metal particles contained in the thin metal wire is preferably 10 to 1000 nm, more preferably 10 to 200 nm, in terms of sphere-equivalent diameter. Note that the sphere-equivalent diameter is the diameter of a spherical particle having the same volume, and the average particle size of the metal particles is obtained by measuring the sphere-equivalent diameters of 100 objects and arithmetically averaging them. The shape of the metal particles is not particularly limited, and examples thereof include spherical, cubic, tabular, octahedral, tetradecahedral, etc. The metal particles may be bonded in part or entirely by fusion.
[0031] The thin metal wire may have a structure in which a plurality of metals are dispersed in a polymer compound described later, or may exist as aggregates in the polymer compound as a result of aggregation of metal particles. Furthermore, at least some of the plurality of metals contained in the thin metal wire may be bonded to each other by a metal derived from metal ions used in a plating process described later. The metal content of the thin metal wires is not particularly limited, and is preferably 3.0 to 20.0 g / m in order to provide a conductive film with superior conductivity. 2 is preferably 5.0 to 15.0 g / m 2 is more preferred.
[0032] (Specific polymer) In the present conductive film, the thin metal wires contain a specific polymer. The type of the specific polymer is not particularly limited as long as it is a polymer compound different from gelatin, and a polymer compound that is not decomposed by a protease or an oxidizing agent that decomposes gelatin, which will be described later, is preferable. The specific polymer may be a hydrophobic (water-insoluble) polymer compound, such as at least one resin selected from the group consisting of (meth)acrylic resins, styrene resins, vinyl resins, polyolefin resins, polyester resins, polyurethane resins, polyamide resins, polycarbonate resins, polydiene resins, epoxy resins, silicone resins, cellulose polymers, and chitosan polymers, or a copolymer consisting of monomers constituting these resins. In addition, the term "hydrophobic" with respect to a compound means that the solubility of the compound in 1 L of water is less than 10 g. In addition, the specific polymer preferably has a reactive group that reacts with a crosslinking agent.
[0033] An example of a preferred embodiment of the specific polymer is a polymer compound containing at least one repeating unit selected from the group consisting of repeating units derived from a styrene-based monomer and repeating units derived from a (meth)acrylate-based monomer. Among them, the specific polymer preferably contains both a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer. In the specific polymer containing both repeating units derived from a styrene-based monomer and repeating units derived from a (meth)acrylate-based monomer, the content of each repeating unit is not particularly limited. The content of the repeating units derived from the styrene-based monomer is preferably 3 to 60 mol%, more preferably 3 to 50 mol%, and even more preferably 3 to 40 mol%, based on the total repeating units contained in the specific polymer. The content of the repeating units derived from the (meth)acrylate-based monomer is preferably 30 to 96 mol%, more preferably 35 to 95 mol%, and even more preferably 40 to 90 mol%, based on the total repeating units contained in the specific polymer.
[0034] The specific polymer containing both a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer is preferably a polymer compound (copolymer) represented by the following general formula (1). General formula (1): -(A) x -(B) y -(C) z -(D) w - In addition, in the general formula (1), A, B, C, and D respectively represent repeating units represented by the following general formulae (A) to (D).
[0035] [ka]
[0036] R 11 represents a methyl group or a halogen atom, and preferably a methyl group, a chlorine atom, or a bromine atom. p represents an integer of 0 to 2, preferably 0 or 1, and more preferably 0. R12 represents a methyl group or an ethyl group, with a methyl group being preferred. R 13 represents a hydrogen atom or a methyl group, and preferably a hydrogen atom. L represents a divalent linking group, and preferably a group represented by the following general formula (2). General formula (2):-(CO-X 1 )rX 2 - In general formula (2), X 1 is an oxygen atom or -NR 30 - where R 30 R represents a hydrogen atom, an alkyl group, an aryl group, or an acyl group, each of which may have a substituent (e.g., a halogen atom, a nitro group, and a hydroxyl group). 30 is preferably a hydrogen atom, an alkyl group having 1 to 10 carbon atoms (such as a methyl group, an ethyl group, an n-butyl group, and an n-octyl group), or an acyl group (such as an acetyl group and a benzoyl group). 1 is preferably an oxygen atom or -NH-. X 2 represents an alkylene group, an arylene group, an alkylenearylene group, an arylenealkylene group, or an alkylenearylenealkylene group, and these groups include -O-, -S-, -CO-, -COO-, -NH-, -SO2-, -N(R 31 )-, or -N(R 31 )SO2- etc. may be inserted in the middle. 31 represents a linear or branched alkyl group having 1 to 6 carbon atoms. 2 is preferably a dimethylene group, a trimethylene group, a tetramethylene group, an o-phenylene group, an m-phenylene group, a p-phenylene group, -CH2CH2OCOCH2CH2-, or -CH2CH2OCO(C6H4)-. r represents 0 or 1. q represents 0 or 1, with 0 being preferred.
[0037] R 14represents an alkyl group, an alkenyl group, or an alkynyl group, preferably an alkyl group having 5 to 50 carbon atoms, more preferably an alkyl group having 5 to 30 carbon atoms, and further preferably an alkyl group having 5 to 20 carbon atoms. R 15 is a hydrogen atom, a methyl group, an ethyl group, a halogen atom, or -CHCOOR 16 represents a hydrogen atom, a methyl group, a halogen atom, or -CH2COOR 16 is preferred, and a hydrogen atom, a methyl group, or -CHCOOR 16 is more preferred, and a hydrogen atom is even more preferred. R 16 represents a hydrogen atom or an alkyl group having 1 to 80 carbon atoms, R 14 may be the same as or different from R 16 The carbon number is preferably 1 to 70, and more preferably 1 to 60.
[0038] In the general formula (1), x, y, z, and w represent the molar ratios of each repeating unit. x is 3 to 60 mol %, preferably 3 to 50 mol %, and more preferably 3 to 40 mol %. y is from 30 to 96 mol %, preferably from 35 to 95 mol %, and more preferably from 40 to 90 mol %. z is from 0.5 to 25 mol %, preferably from 0.5 to 20 mol %, and more preferably from 1 to 20 mol %. w is from 0.5 to 40 mol %, and preferably from 0.5 to 30 mol %. In the general formula (1), it is preferable that x is 3 to 40 mol %, y is 40 to 90 mol %, z is 0.5 to 20 mol %, and w is 0.5 to 10 mol %.
[0039] The polymer represented by the general formula (1) is preferably a polymer represented by the following general formula (2).
[0040] [ka]
[0041] In the general formula (2), x, y, z and w are as defined above.
[0042] The polymer represented by general formula (1) may contain repeating units other than the repeating units represented by the above general formulae (A) to (D). Examples of monomers for forming other repeating units include acrylic acid esters, methacrylic acid esters, vinyl esters, olefins, crotonates, itaconic acid diesters, maleic acid diesters, fumaric acid diesters, acrylamides, unsaturated carboxylic acids, allyl compounds, vinyl ethers, vinyl ketones, vinyl heterocyclic compounds, glycidyl esters, and unsaturated nitriles. These monomers are also described in paragraphs 0010 to 0022 of Japanese Patent No. 3754745. From the viewpoint of hydrophobicity, acrylic acid esters or methacrylic acid esters are preferred, and hydroxyalkyl methacrylate or hydroxyalkyl acrylate is more preferred. The polymer represented by general formula (1) preferably contains a repeating unit represented by general formula (E).
[0043] [ka]
[0044] In the above formula, L E represents an alkylene group, preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 2 to 6 carbon atoms, and further preferably an alkylene group having 2 to 4 carbon atoms.
[0045] As the polymer represented by the general formula (1), a polymer represented by the following general formula (3) is particularly preferable.
[0046] [ka]
[0047] In the above formula, a1, b1, c1, d1 and e1 represent the molar ratio of each repeating unit, where a1 represents 3 to 60 (mol %), b1 represents 30 to 95 (mol %), c1 represents 0.5 to 25 (mol %), d1 represents 0.5 to 40 (mol %), and e1 represents 1 to 10 (mol %). The preferred range of a1 is the same as the preferred range of x above, the preferred range of b1 is the same as the preferred range of y above, the preferred range of c1 is the same as the preferred range of z above, and the preferred range of d1 is the same as the preferred range of w above. e1 is from 1 to 10 mol %, preferably from 2 to 9 mol %, and more preferably from 2 to 8 mol %.
[0048] Another example of a preferred embodiment of the specific polymer is polymer W (hereinafter also simply referred to as "polymer W") obtained by reacting hydrophobic (water-insoluble) polymer X having a crosslinkable group (hereinafter also simply referred to as "polymer X") with hydrophobic (water-insoluble) polymer Y having a reactive group that reacts with the crosslinkable group (hereinafter also simply referred to as "polymer Y"). Polymer W is a polymer compound (copolymer) obtained by reacting a crosslinkable group in polymer X with a reactive group in polymer Y, and has a three-dimensional crosslinked structure formed by polymer X and polymer Y. Hereinafter, polymer W, which is a type of specific polymer, will be explained using polymer X and polymer Y.
[0049] Polymer X is a hydrophobic polymer having a crosslinkable group, and polymer Y is a hydrophobic polymer having a reactive group that reacts with the crosslinkable group. Polymer X and polymer Y react to form polymer W having a three-dimensional crosslinked structure. It is preferable that polymer X and polymer Y are different polymers. Polymer X and polymer Y are each a compound having a plurality of predetermined repeating units. A low molecular weight crosslinking agent does not have a plurality of repeating units like polymer X and polymer Y. The weight average molecular weight of polymer X and polymer Y is preferably 1000 or more. When the weight average molecular weight is 1000 or more, the crosslinking reaction between polymer X and polymer Y is likely to occur selectively, the film strength is increased, and the electrical resistance of the conductive film can be reduced. In particular, the weight average molecular weight of polymer X and polymer Y is preferably 1000 to 1,000,000, more preferably 2000 to 750,000, and even more preferably 3000 to 500,000, in terms of superior properties of the resulting thin metal wire.
[0050] The type of crosslinkable group contained in the polymer X is not particularly limited, and examples thereof include an oxazoline group, a carbodiimide group, an isocyanate group, a carboxyl group, an epoxy group, a carboxylic anhydride group, a halogenated alkyl group, a primary amino group, a secondary amino group, a hydroxyl group, and a vinyl group. The number of crosslinkable groups in the polymer X is not particularly limited, and is often 2 or more. The reactive group contained in the polymer Y is not particularly limited as long as it is a group that reacts with the above-mentioned crosslinkable group, and examples thereof include an oxazoline group, a carbodiimide group, an isocyanate group, a carboxyl group, an epoxy group, a carboxylic anhydride group, a halogenated alkyl group, a primary amino group, a secondary amino group, a hydroxyl group, and a vinyl group. The number of reactive groups in the polymer Y is not particularly limited, and is often 2 or more.
[0051] Suitable combinations of the crosslinkable group of polymer X and the reactive group of polymer Y include, for example, the following combinations (1) to (10), which have better reactivity and result in better properties for the resulting thin metal wire. (1) Oxazoline group and carboxyl group (2) Hydroxyl group and isocyanate group (3) Carboxyl group and epoxy group (4) Hydroxyl group and carboxylic anhydride group (5) Carboxyl group and isocyanate group (6) Amino group and isocyanate group (7) Hydroxyl group and epoxy group (8) Amino and epoxy groups (9) Amino group and alkyl halide (10) Carbodiimide group and carboxyl group In each of the above combinations, one of the two functional groups may be a crosslinkable group and the other may be a reactive group. Specifically, in the case of the above combination (1), the crosslinkable group may be an oxazoline group and the reactive group may be a carboxyl group, or the crosslinkable group may be a carboxyl group and the reactive group may be an oxazoline group. Among the above combinations, the combination of (1), (3) or (10) is preferred, and from the viewpoint of reactivity, the combination of (1) is more preferred. In the case of the combination (1), from the viewpoints of ease of handling and resistance to deactivation of the reactive group, it is preferable that one of the crosslinkable group and the reactive group is an oxazoline group and the other of the crosslinkable group and the reactive group is a carboxyl group. This is because when one of the crosslinkable group and the reactive group is an oxazoline group, it has low reactivity with alcoholic hydroxyl groups that are often contained in water-soluble polymers, and the selectivity of the crosslinking reaction between polymer X and polymer Y is high.
[0052] The main chain structures of polymer X and polymer Y are not particularly limited, and examples thereof include at least one resin selected from the group consisting of (meth)acrylic resins, styrene resins, vinyl resins, polyolefin resins, polyester resins, polyurethane resins, polyamide resins, polycarbonate resins, polydiene resins, epoxy resins, silicone resins, cellulose polymers, and chitosan polymers, or copolymers of monomers constituting these resins. The crosslinkable group and the reactive group may be contained in the side chain or at the end of these resins. The main chain structure of polymer X and polymer Y is preferably the main chain structure of a (meth)acrylic resin, in terms of excellent handleability. As a preferred embodiment of polymer X and polymer Y, from the viewpoints of ease of synthesis and ease of handling, polymer X preferably contains a repeating unit represented by formula (1), and polymer Y preferably contains a repeating unit represented by formula (2).
[0053] [ka]
[0054] In formula (1), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group. R 1 When it is a substituted or unsubstituted alkyl group, it is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 to 2 carbon atoms. More specifically, the unsubstituted alkyl group includes a methyl group, an ethyl group, a propyl group, and a butyl group. The substituted alkyl group includes a methyl group, an ethyl group, a propyl group, and a butyl group, each of which is substituted with a substituent such as a methoxy group. R 1 is preferably a hydrogen atom, a methyl group, or a methyl group substituted with a methoxy group, and more preferably a hydrogen atom.
[0055] In formula (1), L 1 represents a single bond, or a substituted or unsubstituted divalent organic group. Examples of the divalent organic group include a substituted or unsubstituted aliphatic hydrocarbon group (preferably having 1 to 8 carbon atoms), a substituted or unsubstituted aromatic hydrocarbon group (preferably having 6 to 12 carbon atoms), -O-, -S-, -N(R)- (R: alkyl group), -CO-, -NH-, -COO-, -CONH-, and groups combining these (for example, an alkyleneoxy group, an alkyleneoxycarbonyl group, and an alkylenecarbonyloxy group). In formula (1), X represents a crosslinkable group, the definition of which is as described above. The content of the repeating unit represented by formula (1) in the polymer X is not particularly limited, and is preferably from 0.1 to 100 mol %, more preferably from 0.5 to 50 mol %, based on all repeating units.
[0056] In formula (2), R 2 represents a hydrogen atom or a substituted or unsubstituted alkyl group. 1 The preferred embodiments of the alkyl group are the same as those of the alkyl group mentioned above. In formula (2), L2 represents a single bond or a substituted or unsubstituted divalent organic group. The definition of a divalent organic group is 1 The definition of the divalent organic group is the same as that of the divalent organic group. In formula (2), Y represents a reactive group, the definition of which is as described above. The content of the repeating unit represented by formula (2) in polymer Y is not particularly limited, and is preferably from 0.1 to 100 mol %, more preferably from 0.5 to 50 mol %, based on all repeating units.
[0057] Polymer X may have a repeating unit other than the repeating unit represented by formula (1). Polymer Y may have a repeating unit other than the repeating unit represented by formula (2). Examples of the repeating unit other than the repeating unit represented by formula (1) or formula (2) include a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer.
[0058] The specific polymer can be synthesized by referring to, for example, Japanese Patent No. 3305459 and Japanese Patent No. 3754745. The weight average molecular weight of the specific polymer is not particularly limited, and is preferably from 1,000 to 1,000,000, more preferably from 2,000 to 750,000, and further preferably from 3,000 to 500,000.
[0059] The specific polymer is preferably in the form of particles, that is, the thin metal wire preferably contains particles of the specific polymer. The specific polymer may be contained in the various compositions (the composition for forming the underlayer coating film, the composition for forming the upper layer coating film, and the composition for forming the protective layer) in the form of particles. In other words, the specific polymer may be contained in the composition for forming each layer in the form of an emulsion.
[0060] The thin metal wires may further contain materials other than the above-mentioned materials, if necessary. Examples of the additives include antistatic agents, nucleation accelerators, spectral sensitizing dyes, surfactants, antifogging agents, hardeners, antiblack spot agents, redox compounds, monomethine compounds, and dihydroxybenzenes, as described in paragraphs 0220 to 0241 of JP-A-2009-004348. Furthermore, the photosensitive layer may contain physical development nuclei. The thin metal wire may contain a crosslinking agent used for crosslinking the specific polymers together. When the specific polymer contains a crosslinking agent and has a reactive group that reacts with the crosslinking agent, crosslinking between the specific polymers progresses, and the bonds between the metals in the thin metal wire are maintained.
[0061] (gelatin content) In the present conductive film, the thin metal wires do not contain gelatin, or, if they contain gelatin, the gelatin content in the thin metal wires is 0.100 g / m 2 Here, the gelatin content in the thin metal wires is the gelatin content in the thin metal wires per area of the region on the substrate surface where the thin metal wires are arranged. In the present conductive film, the thin metal wires contain metal particles and a specific polymer, and the gelatin content in the thin metal wires is equal to or less than a predetermined amount, so that when the conductive film is applied to a solar cell or an organic EL element, the effect of reducing the change over time in the conversion efficiency of the solar cell or the luminous efficiency of the organic EL element is achieved (hereinafter also referred to as the "effect of the present invention").
[0062] When the thin metal wire contains gelatin, the type of gelatin will be described later. The conductive film is such that the thin metal wire does not contain gelatin, or if it contains gelatin, the gelatin content in the thin metal wire is 0.095 g / m 2 or less, and it is more preferable that the thin metal wires are free of gelatin.
[0063] The gelatin content in the thin metal wire is measured by the BCA method (bicinchoninic acid method). The BCA method is a measurement method that utilizes the property of proteins to reduce alkaline Cu(II) to Cu(I). If silver is present in the thin metal wire, the silver exhibits reducing properties and an accurate measurement value cannot be obtained. Therefore, the thin metal wire is desilvered before the gelatin content is measured by the BCA method. Details of the method for measuring the gelatin content by the BCA method will be explained in the Examples below. A method for forming thin metal wires that contain metal particles and a specific polymer and have a gelatin content of a predetermined amount or less will be described in the method for producing a conductive film described below.
[0064] (Physical properties of thin metal wires) The line width Wa of the thin metal wire is preferably 20 μm or less, more preferably 5 μm or less, and even more preferably 4 μm or less, in order to make the thin metal wire less visible. There is no particular lower limit, but the line width Wa is preferably 0.5 μm or more, and more preferably 1 μm or more, in order to make the thin metal wire more excellent in electrical conductivity. The line width Wa of the above-mentioned thin metal wire is determined by arbitrarily selecting five points equivalent to the line width of one thin metal wire using a scanning electron microscope, and taking the arithmetic mean value equivalent to the line width at the five points as the line width Wa. In this specification, the width direction of the thin metal wire means a direction along the surface of the substrate that is perpendicular to the direction in which the thin metal wire extends, and the line width of the thin metal wire means the total length of the thin metal wire in the width direction.
[0065] The thin metal wire preferably has a line resistance value of less than 200 Ω / mm, and more preferably less than 100 Ω / mm. The linear resistance is the resistance measured by the four-probe method divided by the distance between the measurement terminals. More specifically, after cutting both ends of any one of the metal thin wires constituting the mesh pattern and separating it from the mesh pattern, four microprobes (A, B, C, D) (tungsten probes (diameter 0.5 μm) manufactured by Micro Support Co., Ltd.) are brought into contact with the separated metal thin wire, and a constant current I is applied to the outermost probes A and D using a source meter (KEITHLEY source meter 2400 type general-purpose source meter) so that the voltage V between the inner probes B and C becomes 5 mV, and the resistance value Ri=V / I is measured, and the obtained resistance value Ri is divided by the distance between B and C to obtain the linear resistance value.
[0066] [Transparent conductive layer] In the present conductive film, the transparent conductive layer is disposed at least on the substrate and between the thin metal wires. In the conductive film 10 shown in Fig. 1, the transparent conductive layer 18 is formed over the entire surface so as to cover the surface 12a of the substrate 12 and the metal layer 14. However, the transparent conductive layer is not limited to the embodiment shown in Fig. 1, and as long as it is disposed between the thin metal wires, the transparent conductive layer may be disposed in a pattern along the shape of the electrode so that the conductive film 10 can be used as an electrode. That is, on the surface of the substrate, there may be regions where the transparent conductive layer is disposed (electrode regions) and regions where the transparent conductive layer is not disposed (non-electrode regions). In either case, the transparent conductive layer is provided so as to be in electrical conduction with the metal layer. The method for patterning the transparent conductive layer is not particularly limited, but it is preferable to use a laser ablation method using a laser.
[0067] <Conductive materials> The material constituting the transparent conductive layer is not particularly limited as long as it is a material that is transparent and capable of forming a layer having conductivity, and examples thereof include known materials used for forming transparent electrodes, such as conductive materials.
[0068] The transparent conductive layer may contain conductive fine particles as the conductive material. Examples of the conductive fine particles include conductive metal oxide fine particles, metal fine particles, and carbon nanotubes (CNTs), with conductive metal oxide fine particles being preferred. Examples of conductive metal oxides include metal oxides such as tin oxide (SnO2), zinc oxide (ZnO), titanium oxide (TiO2), aluminum oxide (Al2O3), indium oxide (In2O3), magnesium oxide (MgO), barium oxide (BaO), and molybdenum oxide (MoO3), as well as composite oxides of these metal oxides and composite oxides containing heteroatoms such as antimony (Sb) and fluorine (F). The metal oxide is preferably SnO2, ZnO, TiO2, Al2O3, In2O3 or MgO, more preferably SnO2, and more preferably SnO2 doped with antimony, particularly preferably SnO2 doped with 0.2 to 2.0 mol % of antimony.
[0069] The shape of the conductive fine particles is not particularly limited, and examples thereof include granular and needle-like shapes. The conductive fine particles preferably have an average particle diameter (equivalent sphere diameter) of 0.005 to 0.12 μm. The lower limit of the average particle diameter is more preferably 0.008 μm, and even more preferably 0.01 μm. The upper limit of the average particle diameter is more preferably 0.08 μm, and even more preferably 0.05 μm. By satisfying the above average particle diameter conditions, the conductive fine particles can form a conductive layer that is excellent in transparency and has uniform conductivity in the in-plane direction. As conductive fine particles having the above-mentioned characteristics, the SN series and FS series manufactured by Ishihara Sangyo Kaisha, Ltd., and conductive materials manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd. can be used.
[0070] The content of the conductive fine particles in the transparent conductive layer is 0.05 to 0.99 g / m 2 The lower limit is preferably within the range of 0.1 g / m 2 More preferably, 0.2 g / m 2 The upper limit is more preferably 0.5 g / m 2More preferably, 0.45 g / m 2 is more preferred.
[0071] The transparent conductive layer may also contain a conductive polymer as the conductive material. The conductive polymer refers to a polymer compound having electrical conductivity. The charge transported by the conductive polymer may be either hole-conductive or electron-conductive. Examples of conductive polymers include polythiophene, polypyrrole, polyaniline, polyphenylenevinylene, polyphenylene, polyacetylene, polyquinoxaline, polyoxadiazole, and polybenzothiadiazole, as well as polymers having a plurality of these skeletal structures. Among them, polythiophene is preferred as the conductive polymer, and polyethylenedioxythiophene is more preferred. These polythiophenes are usually partially oxidized to obtain conductivity. The conductivity of the conductive polymer can be adjusted by the degree of partial oxidation (doping amount), and the higher the doping amount, the higher the conductivity. Since polythiophene becomes cationic by partial oxidation, it has a counter anion to neutralize the charge. An example of such a polythiophene is polyethylenedioxythiophene (PEDOT-PSS) with polystyrene sulfonic acid as the counter ion, and it is particularly preferable to use PEDOT-PSS as the conductive polymer.
[0072] <Binder> The transparent conductive layer may contain other components other than the above-mentioned conductive materials as long as the conductivity is not impaired. Examples of other components include a binder. The binder is used for the purpose of improving the coatability of the coating solution used to form the transparent conductive layer and improving the film strength. In particular, when the transparent conductive layer contains the above-mentioned conductive fine particles as a conductive material, it is preferable that the transparent conductive layer contains a binder, since this allows the conductive fine particles to be dispersed more uniformly in the transparent conductive layer and improves the bonding strength of the transparent conductive layer to the substrate.
[0073] As the binder contained in the transparent conductive layer, a polymer compound can be used. The transparent conductive layer preferably contains the above-mentioned specific polymer as a binder. More preferred embodiments of the binder include the preferred embodiments of the above-mentioned specific polymer. Among them, as the binder, a polymeric compound containing at least one repeating unit selected from the group consisting of a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer is preferred, and a polymeric compound containing both a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer is more preferred. In addition, it is preferable that the binder contained in the transparent conductive layer and the specific polymer contained in the thin metal wires are the same polymer compound.
[0074] The transparent conductive layer preferably has an aspect containing conductive fine particles (more preferably conductive metal oxide fine particles) and a binder, or an aspect containing a conductive polymer. The transparent conductive layer may contain other components in addition to the above-mentioned conductive material and binder, such as various solvents, surfactants, thickeners, and other additives contained in the composition for forming the transparent conductive layer.
[0075] The thickness of the transparent conductive layer is preferably within the range of 50 nm to 50 μm, and more preferably within the range of 100 nm to 2 μm. The transparent conductive layer may be thinner than the metal layer or may be substantially the same thickness as the metal layer. The transparent conductive layer may be thicker than the metal layer and may be formed so as to cover the surface of the metal layer. The volume resistivity of the transparent conductive layer is 5×10 -1 Ωcm or less is preferable, 5×10 -2 The lower limit is not particularly limited, and is preferably 1×10 -4 It may be Ωcm or more.
[0076] The method for forming the transparent conductive layer is not particularly limited, and the layer can be formed by a known method. The transparent conductive layer may be formed, for example, by carrying out step J or step K in the method for producing a conductive film described below. The transparent conductive layer can be formed by applying a coating liquid containing the material for forming the transparent conductive layer to the surface of the substrate and drying the coating film. The coating liquid may contain various additives such as solvents, surfactants, and thickeners as coating aids.
[0077] [Other components] The conductive film may have other members in addition to the above-mentioned substrate, metal layer, and transparent conductive layer. An example of another member that the conductive film may have is an intermediate layer that contains a specific polymer as a main component and is disposed between the substrate and the metal layer. The specific polymer contained in the intermediate layer, including its preferred embodiments, may be the same as the polymer compound described as the specific polymer contained in the thin metal wires. In particular, it is preferable that the intermediate layer contains the same polymer compound as the specific polymer contained in the thin metal wires. The content of the specific polymer in the intermediate layer is preferably 90% by mass or more, more preferably 95% by mass or more, based on the total mass of the intermediate layer. The upper limit is not particularly limited, and may be 100% by mass based on the total mass of the intermediate layer, or, in the case where an additive such as a colorant is contained, may be the remainder excluding the additive. The intermediate layer may contain a coloring agent such as a dye in order to function as an antihalation layer. In addition, it is preferable that the intermediate layer does not contain a conductive metal. The method for forming the intermediate layer is not particularly limited. For example, an intermediate layer containing a specific polymer as a main component is formed by carrying out step H for forming an intermediate layer in the method for producing a conductive film described below.
[0078] The conductive film may have, for example, a protective layer that contains a specific polymer as a main component and is formed on the surface of the metal layer opposite to the substrate. The specific polymer contained in the protective layer, including its preferred embodiments, may be the same as the polymer compound described as the specific polymer contained in the thin metal wires. In particular, the protective layer preferably contains the same polymer compound as the specific polymer contained in the thin metal wires. The content of the specific polymer in the protective layer is preferably 90% by mass or more, more preferably 95% by mass or more, based on the total mass of the protective layer. The upper limit is not particularly limited, and may be 100% by mass, based on the total mass of the protective layer. In addition, it is preferable that the protective layer does not contain a conductive metal. The method for forming the protective layer is not particularly limited. For example, a protective layer containing a specific polymer as a main component is formed by carrying out step I for forming a protective layer in the method for producing a conductive film described below.
[0079] In addition to the metal layer and the transparent conductive layer made of thin metal wires, the conductive film may have a conductive part having a different configuration from both the metal layer and the transparent conductive layer. This conductive part may be electrically connected to the thin metal wires and be conductive. Examples of the conductive part include peripheral wiring having a function of applying a voltage to the thin metal wires, and alignment marks for adjusting the position of the conductive film and the member to be laminated.
[0080] [Method for producing conductive film] Next, a method for producing the conductive film will be described. The method for producing the conductive film is not particularly limited as long as it can produce the conductive film of the above-mentioned configuration, and known methods are adopted.For example, the method of performing exposure and development using silver halide, the method of forming a metal-containing layer on the entire surface of a substrate, removing a part of the metal-containing layer using a resist pattern to form a thin-line metal-containing layer, and then forming a transparent conductive layer on the entire surface of the substrate on which the thin-line metal-containing layer is formed, and the method of ejecting a composition containing metal and resin onto a substrate by a known printing method such as inkjet to form a thin-line metal-containing layer, and then forming a transparent conductive layer on the entire surface of the substrate on which the thin-line metal-containing layer is formed. Among them, the method of performing exposure and development using silver halide is preferred in terms of superior productivity and electrical conductivity of the metal thin wires.Specifically, the method includes a method of manufacturing a conductive film by performing steps A to D described later in this order to form a thin line-shaped metal-containing layer on a substrate, and performing step J or K described later to form a transparent conductive layer on the entire surface of the substrate on which the thin line-shaped metal-containing layer is formed. Hereinafter, a method for producing a conductive film including steps A to D and step J or K will be described in detail, but the method for producing a conductive film is not limited to the following method.
[0081] <Process A> Step A is a step of forming a silver halide-containing photosensitive layer (hereinafter also referred to as "photosensitive layer") containing silver halide, gelatin, and a specific polymer (a polymer compound different from gelatin) on a substrate. This step produces a substrate with a photosensitive layer that is to be subjected to an exposure treatment described later. First, the materials and components used in process A will be described in detail, and then the procedure of process A will be described in detail. The substrate and the specific polymer used in step A are as described above.
[0082] (Silver halide) The halogen atom contained in silver halide may be any of chlorine atom, bromine atom, iodine atom and fluorine atom, or may be a combination of these.For example, silver halide mainly made of silver chloride, silver bromide or silver iodide is preferred, and silver halide mainly made of silver chloride or silver bromide is more preferred.In addition, silver chlorobromide, silver iodochlorobromide or silver iodobromide is also preferably used. Here, for example, "silver halide mainly composed of silver chloride" refers to a silver halide in which the molar fraction of chloride ions in the total halide ions in the silver halide composition is 50% or more. This silver halide mainly composed of silver chloride may contain bromide ions and / or iodide ions in addition to chloride ions.
[0083] The silver halide is usually in the form of solid particles, and the average particle size of the silver halide is preferably 10 to 1000 nm, more preferably 10 to 200 nm, in terms of equivalent sphere diameter, and further preferably 50 to 150 nm, in that the change in resistance value of the thin metal wire is smaller in a moist and hot environment. The equivalent sphere diameter is the diameter of a spherical particle having the same volume. The "sphere-equivalent diameter" used as the average grain size of the silver halide mentioned above is an average value, which is obtained by measuring the sphere-equivalent diameters of 100 silver halide grains and calculating the arithmetic mean thereof. The same applies to the average grain sizes of other grains described in this specification.
[0084] The shape of the silver halide grains is not particularly limited, and examples thereof include spherical, cubic, tabular (hexagonal tabular, triangular tabular, rectangular tabular, etc.), octahedral, and tetradecahedral shapes.
[0085] (gelatin) The type of gelatin is not particularly limited, and examples thereof include lime-processed gelatin and acid-processed gelatin. In addition, gelatin hydrolysates, gelatin enzymatic decomposition products, and gelatins modified with amino groups and / or carboxyl groups (phthalated gelatin and acetylated gelatin) may also be used.
[0086] The photosensitive layer contains the specific polymer described above. By containing this specific polymer in the photosensitive layer, the strength of the thin metal wire formed from the photosensitive layer is further improved.
[0087] (Step A Procedure) The method for forming the photosensitive layer containing the above-mentioned components in step A is not particularly limited, but from the viewpoint of productivity, a method in which a composition for forming a photosensitive layer containing silver halide, gelatin, and a specific polymer is brought into contact with a substrate to form a photosensitive layer on the substrate is preferred. The form of the photosensitive layer forming composition used in this method will be described in detail below, and then the steps will be described in detail.
[0088] (Materials contained in the composition for forming the photosensitive layer) The photosensitive layer forming composition contains the above-mentioned silver halide, gelatin, and specific polymer. If necessary, the specific polymer may be contained in the photosensitive layer forming composition in the form of particles. The photosensitive layer forming composition may contain a solvent, if necessary. Solvents include water, organic solvents (eg, alcohols, ketones, amides, sulfoxides, esters and ethers), ionic liquids, and mixtures thereof.
[0089] The method for contacting the composition for forming a photosensitive layer with the substrate is not particularly limited, and examples thereof include a method of applying the composition for forming a photosensitive layer onto the substrate, and a method of immersing the substrate in the composition for forming a photosensitive layer. After the above treatment, a drying treatment may be carried out, if necessary.
[0090] (Silver halide-containing photosensitive layer) The photosensitive layer formed by the above procedure contains silver halide, gelatin and a specific polymer. The content of silver halide in the photosensitive layer is not particularly limited, but is preferably 3.0 to 20.0 g / m2 in terms of silver, since this provides a conductive film with superior conductivity. 2 is preferably 5.0 to 15.0 g / m 2 The term "silver equivalent" means that the silver halide is converted into the mass of silver produced by reducing all of the silver halide. The content of the specific polymer in the photosensitive layer is not particularly limited, and is preferably 0.04 to 2.0 g / m in order to provide a conductive film with superior conductivity. 2 is preferably 0.08 to 0.40 g / m 2 More preferably, 0.10 to 0.40 g / m 2 is more preferred.
[0091] <Process B> Step B is a step of exposing the photosensitive layer to light and then developing it to form a fine line-shaped silver-containing layer that contains metallic silver, gelatin, and a specific polymer.
[0092] By subjecting the photosensitive layer to an exposure process, a latent image is formed in the exposed areas. Exposure may be carried out in a pattern. For example, in order to obtain a mesh pattern consisting of the above-mentioned thin metal wires, examples of the method include a method of exposing through a mask having a mesh-shaped opening pattern, and a method of exposing in a mesh pattern by scanning with laser light. The type of light used for exposure is not particularly limited as long as it can form a latent image in the silver halide, and examples of such light include visible light, ultraviolet light, and X-rays.
[0093] By subjecting the exposed photosensitive layer to a development process, metallic silver is precipitated in the exposed areas (areas where a latent image is formed). The method of development is not particularly limited, and examples thereof include known methods used for silver halide photographic films, photographic papers, films for printing plate making, and emulsion masks for photomasks. In the development process, a developer is usually used. The type of developer is not particularly limited, and examples thereof include PQ (phenidone hydroquinone) developer, MQ (metol hydroquinone) developer, and MAA (metol ascorbic acid) developer.
[0094] This process may further include a fixing treatment for the purpose of removing and stabilizing the silver halide in the unexposed areas. Fixing treatment is carried out simultaneously with and / or after development. The fixing method is not particularly limited, and examples thereof include methods used for silver halide photographic film, photographic paper, film for printing plate making, and emulsion masks for photomasks. In the fixing process, a fixing solution is usually used. The type of fixing solution is not particularly limited, and examples thereof include the fixing solutions described on page 321 of "Chemistry of Photography" (by Sasai, Shashin Kogyo Publishing Co., Ltd.).
[0095] By carrying out the above-mentioned treatment, a thin-line silver-containing layer containing metallic silver, gelatin, and a specific polymer is formed. In addition, when carrying out simultaneous multilayer coating in which at least one of the steps H and I (or J) described below is carried out simultaneously with the step A, a silver-free layer not containing metallic silver but containing gelatin and a specific polymer is formed. The width of the silver-containing layer can be adjusted, for example, by adjusting the opening width of a mask used during exposure. For example, the exposed area can be adjusted by setting the opening width of the mask to 1 to 5 μm. In addition, when using a mask during exposure, the width of the silver-containing layer formed can also be adjusted by adjusting the amount of exposure.For example, when the opening width of the mask is narrower than the width of the silver-containing layer to be targeted, the width of the region in which the latent image is formed can be adjusted by increasing the amount of exposure more than usual.In other words, the line width of the thin metal wire can be adjusted by the amount of exposure. Furthermore, when a laser beam is used, the exposure area can be adjusted by adjusting the focusing range and / or scanning range of the laser beam.
[0096] The width of the silver-containing layer is preferably 1 to 5 μm, and more preferably 4 μm or less, since the formed thin metal wires are difficult to visually recognize. The silver-containing layer obtained by the above procedure is in the form of thin lines, and the width of the silver-containing layer means the length (width) of the silver-containing layer in a direction perpendicular to the direction in which the thin lines of the silver-containing layer extend.
[0097] <Process C> Step C is a step of subjecting the silver-containing layer obtained in step B, and optionally the above-mentioned non-silver-containing layer (hereinafter also referred to as "silver-containing layer, etc.", including the case where a non-silver-containing layer is formed), to a heat treatment. By carrying out this step, fusion between specific polymers in the silver-containing layer, etc. progresses, and the strength of the silver-containing layer, etc. is improved.
[0098] The method of heat treatment is not particularly limited, and examples thereof include a method of contacting the silver-containing layer, etc. with superheated steam, and a method of heating with a temperature control device (e.g., a heater), with the method of contacting the silver-containing layer, etc. with superheated steam being preferred.
[0099] The superheated steam may be superheated water vapor or a mixture of superheated water vapor and other gases. The contact time between the superheated steam and the silver-containing layer, etc. is not particularly limited, and is preferably 10 to 70 seconds. The supply rate of superheated steam is 500-600g / m 3 The temperature of the superheated steam is preferably 100 to 160° C. (preferably 100 to 120° C.) at 1 atmospheric pressure.
[0100] In the method of heating the silver-containing layer etc. with a temperature regulator, heating conditions are preferably 100 to 200° C. (preferably 100 to 150° C.) for 1 to 240 minutes (preferably 60 to 150 minutes).
[0101] <Process D> Step D is a step of removing gelatin from the silver-containing layer etc. obtained in step C. By carrying out this step, gelatin is removed from the silver-containing layer etc., and spaces are formed inside the silver-containing layer etc.
[0102] The method for removing gelatin is not particularly limited, and examples thereof include a method using a protease (hereinafter also referred to as "Method 1") and a method for decomposing and removing gelatin using an oxidizing agent (hereinafter also referred to as "Method 2").
[0103] The proteolytic enzyme used in Method 1 includes known plant or animal enzymes capable of hydrolyzing proteins such as gelatin. Examples of proteolytic enzymes include pepsin, rennin, trypsin, chymotrypsin, cathepsin, papain, ficin, thrombin, renin, collagenase, bromelain, and bacterial proteases, with trypsin, papain, ficin, and bacterial proteases being preferred. The procedure in method 1 may be any method that brings the silver-containing layer etc. into contact with the protease, such as a method of bringing the silver-containing layer etc. into contact with a treatment liquid containing a protease (hereinafter also referred to as "enzyme liquid"). Examples of the contact method include a method of immersing the silver-containing layer etc. in the enzyme liquid, and a method of applying the enzyme liquid onto the silver-containing layer etc. The content of the protease in the enzyme solution is not particularly limited, and is preferably 0.05 to 20% by mass, more preferably 0.5 to 10% by mass, based on the total amount of the enzyme solution, in that the degree of decomposition and removal of gelatin is easily controlled. The enzyme solution often contains water in addition to the above-mentioned proteolytic enzymes. The enzyme solution may contain other additives (eg, pH buffering agents, antibacterial compounds, wetting agents, and preservatives) as necessary. The pH of the enzyme solution is selected so as to obtain maximum activity of the enzyme, and is preferably 5 to 9. The temperature of the enzyme solution is preferably a temperature at which the activity of the enzyme is enhanced, specifically, 20 to 45°C.
[0104] If necessary, after the treatment with the enzyme solution, a washing treatment may be carried out in which the obtained silver-containing layer, etc. is washed with warm water. The washing method is not particularly limited, and a method of contacting the silver-containing layer etc. with warm water is preferred. Examples of the method include a method of immersing the silver-containing layer etc. in warm water and a method of applying warm water onto the silver-containing layer etc. The temperature of the hot water is appropriately selected optimally depending on the type of protease used, and from the viewpoint of productivity, a temperature of 20 to 80°C is preferable, and 40 to 60°C is more preferable. The contact time (washing time) between the hot water and the silver-containing layer or the like is not particularly limited, and from the viewpoint of productivity, it is preferably from 1 to 600 seconds, more preferably from 30 to 360 seconds.
[0105] The oxidizing agent used in Method 2 may be any oxidizing agent capable of decomposing gelatin, and is preferably an oxidizing agent having a standard electrode potential of +1.5 V or higher. The standard electrode potential here refers to the standard electrode potential (25° C., E0) of the oxidizing agent in an aqueous solution with respect to a standard hydrogen electrode. Examples of the oxidizing agent include persulfuric acid, percarbonic acid, perphosphoric acid, hypoperchloric acid, peracetic acid, metachloroperbenzoic acid, hydrogen peroxide, perchloric acid, periodic acid, potassium permanganate, ammonium persulfate, ozone, hypochlorous acid or a salt thereof, and the like. From the viewpoints of productivity and economy, however, hydrogen peroxide (standard electrode potential: 1.76 V), hypochlorous acid or a salt thereof are preferred, and sodium hypochlorite is more preferred.
[0106] The procedure in method 2 may be any method that brings the silver-containing layer etc. into contact with the above-mentioned oxidizing agent, for example, a method of bringing the silver-containing layer etc. into contact with a treatment liquid containing an oxidizing agent (hereinafter also referred to as "oxidizing agent liquid"). Examples of the contact method include a method of immersing the silver-containing layer etc. in the oxidizing agent liquid and a method of applying the oxidizing agent liquid onto the silver-containing layer etc. The type of solvent contained in the oxidizing agent liquid is not particularly limited, and examples thereof include water and organic solvents.
[0107] <Process E> The method for producing a conductive film may include a step E of plating the silver-containing layer obtained in the step D. By carrying out this step, the internal space of the silver-containing layer formed by removing the gelatin can be filled with a metal (plating metal), thereby improving the conductivity of the thin metal wires.
[0108] The type of plating is not particularly limited, but examples include electroless plating (chemical reduction plating or displacement plating) and electrolytic plating, with electroless plating being preferred. As the electroless plating, a known electroless plating technique is used. Examples of plating treatments include silver plating treatment, copper plating treatment, nickel plating treatment, and cobalt plating treatment. In terms of superior conductivity of the thin metal wires, silver plating treatment or copper plating treatment is preferred, with silver plating treatment being more preferred.
[0109] The components contained in the plating solution used in the plating process are not particularly limited, but in general, in addition to a solvent (e.g., water), the plating solution mainly contains 1. metal ions for plating, 2. a reducing agent, 3. an additive (stabilizer) for improving the stability of the metal ions, and 4. a pH adjuster. In addition to these, the plating bath may contain known additives such as a stabilizer for the plating bath. The type of metal ion contained in the plating solution for plating can be appropriately selected depending on the type of metal to be deposited, and examples thereof include silver ions, copper ions, nickel ions, and cobalt ions.
[0110] The procedure for the above plating treatment is not particularly limited as long as it is a method for contacting the silver-containing layer with a plating solution, and examples thereof include a method of immersing the silver-containing layer in a plating solution and a method of applying a plating solution to the silver-containing layer. The contact time between the silver-containing layer and the plating solution is not particularly limited, and is preferably 20 seconds to 30 minutes from the standpoint of superior conductivity of the thin metal wires and productivity.
[0111] <Process F> The method for producing a conductive film may further include a step F of subjecting the silver-containing layer and the like obtained in the above steps to a smoothing treatment.
[0112] The method of the smoothing treatment is not particularly limited, and for example, a calendering process in which a substrate having a silver-containing layer or the like is passed between at least a pair of rolls under pressure is preferred. Hereinafter, the smoothing treatment using a calender roll will be referred to as calendering. The rolls used in the calendar treatment include plastic rolls and metal rolls, with plastic rolls being preferred from the viewpoint of preventing wrinkles. The pressure between the rolls is not particularly limited, and is preferably 2 MPa or more, more preferably 4 MPa or more, and is preferably 120 MPa or less. The pressure between the rolls can be measured using a Prescale (for high pressure) manufactured by FUJIFILM Corporation. The temperature for the smoothing treatment is not particularly limited, but is preferably from 10 to 100°C, and more preferably from 10 to 50°C.
[0113] <Process G> The method for producing a conductive film may include a step G of subjecting the silver-containing layer obtained in the above step to a heat treatment. By carrying out this step, thin metal wires with superior conductivity can be obtained. The method for subjecting the thin metal wires to the heat treatment is not particularly limited, and the methods described in step C can be mentioned.
[0114] <Process H> The method for producing a conductive film may include a step H of forming an intermediate layer containing a specific polymer on a substrate before the step A. By carrying out this step, an intermediate layer is formed between the substrate and the silver halide-containing photosensitive layer. This intermediate layer plays the role of a so-called antihalation layer and contributes to improving the adhesion between the thin metal wires and the substrate. As described below, the step H may be carried out simultaneously with the step A. The intermediate layer contains the specific polymer described above, but does not contain silver halide. The content of the specific polymer in the intermediate layer is not particularly limited, and is up to 0.03 g / m 2 In most cases, the adhesion of the metal wire is superior, so 1.0 g / m 2 The upper limit is not particularly limited, but is preferably 1.63 g / m 2 The following are often the cases:
[0115] The method for forming the intermediate layer is not particularly limited. For example, an intermediate layer is formed by applying a composition for forming an intermediate layer containing gelatin and a specific polymer onto a substrate, subjecting the formed coating film to a heat treatment as necessary, and then removing the gelatin from the coating film according to the above-mentioned step D. The composition for forming the intermediate layer may contain a solvent, if necessary. The type of the solvent may be the same as that used in the composition for forming the photosensitive layer described above. The thickness of the intermediate layer is not particularly limited, and is often 0.05 μm or more. In terms of better adhesion to the thin metal wire, the thickness is preferably more than 1.0 μm, and more preferably 1.5 μm or more. The upper limit is not particularly limited, but it is preferably less than 3.0 μm.
[0116] <Process I> The method for producing a conductive film may include a step I of forming a protective layer containing a specific polymer on the silver halide-containing photosensitive layer after step A and before step B. By providing a protective layer, the scratch resistance and mechanical properties of the photosensitive layer can be improved. As described below, step I may be performed simultaneously with step A. The content of the specific polymer in the protective layer is not particularly limited, and is not more than 0 g / m 2 Super 0.3g / m 2 The preferred range is 0.005 to 0.1 g / m or less. 2 is more preferred.
[0117] The method for forming the protective layer is not particularly limited. For example, a protective layer is formed by applying a protective layer-forming composition containing a specific polymer onto a silver halide-containing photosensitive layer, and then subjecting the formed coating film to a heat treatment as necessary, and then removing gelatin from the coating film according to the above-mentioned step D. The composition for forming a protective layer may contain a solvent, if necessary. The type of the solvent may be the same as that used in the composition for forming a photosensitive layer described above. The thickness of the protective layer is not particularly limited, but is preferably from 0.03 to 0.3 μm, and more preferably from 0.075 to 0.20 μm.
[0118] The above-mentioned steps H, A, and I (and / or step J described below) may be carried out simultaneously by simultaneous multilayer coating.
[0119] The method for producing a conductive film further includes step J or step K as a step of forming a transparent conductive layer.
[0120] <Process J> Process J is a process, which is carried out simultaneously with or after process A and before process B, of forming a transparent conductive layer precursor layer (hereinafter also simply referred to as "precursor layer") containing a conductive material and a specific polymer on the silver halide-containing photosensitive layer. Step J may be the same as step I, except that a composition for forming a transparent conductive layer containing a conductive material is used instead of the composition for forming a protective layer. Step J may be carried out instead of step I, or may be carried out in addition to step I.
[0121] The conductive material contained in the composition for forming a transparent conductive layer used in step J, including its preferred embodiments, may be the same as the conductive material contained in the transparent conductive layer, and is appropriately selected depending on the desired transparent conductive layer. The transparent conductive layer-forming composition used in step J preferably contains conductive fine particles, more preferably contains conductive metal oxide fine particles, and preferably contains a binder, more preferably contains a specific polymer. The content of the conductive material and the binder (more preferably the specific polymer) in the transparent conductive layer forming composition is not particularly limited, and is appropriately selected according to the composition of the intended transparent conductive layer. In addition, the transparent conductive layer forming composition may contain a solvent as necessary. The type of the solvent is exemplified by the solvent used in the photosensitive layer forming composition described above. After forming the precursor layer in step J, the precursor layer is subjected to a heat treatment as necessary, and then the gelatin is removed from the coating film according to step D above, thereby forming a transparent conductive layer.
[0122] <Process K> Step K is a step of forming a metal layer composed of thin metal wires on a substrate according to the above-mentioned manufacturing method having steps A to D and optionally at least one of steps E to H, and then forming a transparent conductive layer on the metal layer using a transparent conductive layer-forming composition containing a conductive material. The method for forming the transparent conductive layer is not particularly limited, and examples thereof include a method (coating method) of coating the above composition on the surface of the substrate on which the metal layer is formed to form a transparent conductive layer, and a method (transfer method) of forming a transparent conductive layer on a temporary support using the above composition and transferring it to the surface of the substrate.Among these, the coating method is preferred in terms of easy thickness control.
[0123] The conductive material contained in the composition for forming a transparent conductive layer used in step K, including its preferred embodiments, may be the same as the conductive material contained in the transparent conductive layer, and is appropriately selected depending on the desired transparent conductive layer. The transparent conductive layer forming composition used in the step K preferably contains a conductive polymer. The transparent conductive layer forming composition may also contain a solvent as necessary. The type of solvent may be the solvent used in the photosensitive layer forming composition described above, and preferably contains at least water. The transparent conductive layer forming composition may also contain a binder, and a coating aid such as a surfactant and a thickener. The contents of the conductive material, solvent and binder in the composition for forming a transparent conductive layer are not particularly limited and are appropriately selected depending on the composition of the intended transparent conductive layer, ease of formation, and the like.
[0124] [Uses of conductive films] The conductive film can be used for various purposes, and can be particularly suitably used as a transparent electrode for elements such as organic EL elements, solar cells, touch panels, and inorganic EL elements. In particular, the conductive film can be used as a transparent electrode for flexible electronic devices such as flexible solar cells and flexible organic EL elements, since a transparent electrode with excellent flexibility can be formed on a flexible substrate. The conductive film can also be applied to fields of application where a large-area conductive element is required, such as an electrode for an electrochromic device used in a window having a dimming function that reduces the illuminance of incident light or blocks incident light. This conductive film can also be used as an electromagnetic wave shield to block electromagnetic waves such as radio waves and microwaves (ultra-high frequency waves) generated by electronic devices such as personal computers and workstations, and to prevent static electricity. Such electromagnetic wave shields can be used not only in personal computers, but also in electronic devices such as video recording equipment and electronic medical devices. The conductive film can also be used as a transparent heating element and can be applied to electrode structures such as vehicle defrosters and window glass.
[0125] The conductive film may be used in the form of a laminate having the conductive film and other members such as an adhesive sheet and a release sheet during handling and transportation. The release sheet functions as a protective sheet for preventing the conductive film from being scratched during transportation of the laminate. The conductive film may also be handled in the form of a composite having, for example, a conductive film, an adhesive sheet, and a protective layer in this order.
[0126] [Solar cell] A solar cell having the present conductive film will now be described. The solar cell having the conductive film is not particularly limited as long as the conductive film is used as at least one of a pair of electrodes. In particular, a flexible solar electrode is preferable as the solar cell having the conductive film. Examples of the flexible solar cell include organic solar cells such as perovskite solar cells, dye-sensitized solar cells, and organic thin-film solar cells. Examples of the solar cell include a solar cell that includes a substrate, a first transparent electrode, a bulk hetero layer, and a second transparent electrode, and at least one of the first transparent electrode and the second transparent electrode is the conductive film. From the viewpoint of excellent durability, it is preferable that the solar cell has the present conductive film as a first transparent electrode and a light-transmitting thin film containing a precious metal as a main component as a second transparent electrode. In addition, the solar cell may further have, if desired, a known layer such as a hole blocking layer, an electron blocking layer, an exciton diffusion preventing layer, a hole transporting layer, an electron transporting layer, a hole collecting layer, an electron collecting layer, an easy-adhesion layer, a protective layer, a conductive layer, a gas barrier layer, a matting agent layer, an antireflection layer, a hard coat layer, an antifogging layer, and an antifouling layer.
[0127] The method for producing the solar cell is not particularly limited, and the solar cell can be produced according to a known method, except that the conductive film is used for at least one of the pair of electrodes. By using this conductive film, it is possible to manufacture a solar cell that exhibits little change in conversion efficiency over time and has excellent stability over time.
[0128] [Organic EL element] An organic EL device having the conductive film will now be described. The conductive film can be used, for example, as an anode of an organic EL element. Preferably, the conductive film can be used as an anode of a flexible organic EL element. The light-emitting layer (also called an organic light-emitting layer) and the cathode of the organic EL element having the conductive film as the anode can be appropriately selected from materials and configurations that are generally used in organic EL elements.
[0129] The element configuration of the organic EL element can be exemplified by the following configurations, but is not limited thereto. (1) Anode / light-emitting layer / cathode. (2) anode / hole transport layer / light emitting layer / electron transport layer / cathode. (3) anode / hole injection layer / hole transport layer / light emitting layer / electron transport layer / cathode. (4) anode / hole injection layer / light-emitting layer / electron transport layer / electron injection layer / cathode. (5) anode / hole injection layer / light-emitting layer / electron injection layer / cathode.
[0130] As for the light-emitting material and doping material contained in the light-emitting layer of the organic EL element, known light-emitting materials and doping materials used in organic EL elements can be appropriately used. The method for producing the organic EL element is not particularly limited, and the organic EL element can be produced by a known method using the present conductive film as the anode. An organic EL device comprising the present conductive film can be used in self-luminous displays, liquid crystal backlights, lighting, and the like. By using this conductive film, it is possible to manufacture organic EL devices that exhibit little change in luminous efficiency over time and have excellent stability over time.
[0131] The present invention is basically configured as described above. The present invention is not limited to the above-described embodiment, and various improvements and modifications may be made without departing from the spirit and scope of the present invention. EXAMPLES
[0132] The present invention will be described in more detail below with reference to examples. Note that the materials, amounts, ratios, processing contents, and processing procedures shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0133] [Example 1] [Preparation of Emulsion 1] To the following solution 1, which was kept at 38°C and pH 4.5, 90% of each of the following solutions 2 and 3 were added simultaneously over a period of 20 minutes while stirring the solution 1, forming core particles of 0.16 μm. Next, the following solutions 4 and 5 were added to the resulting solution over a period of 8 minutes, and the remaining 10% of the following solutions 2 and 3 were added over a period of 2 minutes to grow the core particles to 0.21 μm. Furthermore, 0.15 g of potassium iodide was added to the resulting solution, which was then aged for 5 minutes to complete the particle formation.
[0134] 1 liquid: 750mL water Gelatin (phthalated gelatin) 8g Sodium chloride 3g 1,3-Dimethylimidazolidine-2-thione 20mg Sodium benzenethiosulfonate 10mg Citric acid 0.7g 2 liquid: 300mL water Silver nitrate 150g 3 liquid: 300mL water Sodium chloride 38g 32g potassium bromide Potassium hexachloroiridate(III) (0.005%KCl 20% aqueous solution) 5mL Ammonium hexachlororhodate (0.001%NaCl 20% aqueous solution) 7mL 4 liquid: 100mL water Silver nitrate 50g 5 liquid: 100mL water Sodium chloride 13g Potassium bromide 11g Yellow prussia 5mg
[0135] Then, the emulsion was washed by the flocculation method according to the usual method. Specifically, the temperature of the above-obtained solution was lowered to 35°C, 3 liters of distilled water was added, and the pH was lowered using sulfuric acid until the silver halide precipitated (pH was in the range of 3.6±0.2). Next, about 3 liters of the supernatant was removed from the obtained solution (first washing). To the solution from which the supernatant was removed, another 3 liters of distilled water was added, and sulfuric acid was added until the silver halide precipitated. Again, 3 liters of the supernatant was removed from the obtained solution (second washing). The same operation as the second washing was repeated once more (third washing), and the washing and desalting process was completed. The emulsion after washing and desalting was adjusted to pH 6.4 and pAg 7.5, and 10 mg of sodium benzenethiosulfonate, 3 mg of sodium benzenethiosulfinate, 15 mg of sodium thiosulfate, and 10 mg of chloroauric acid were added, and chemical sensitization was performed at 55°C to obtain the optimum sensitivity. Then, 100 mg of 1,3,3a,7-tetraazaindene as a stabilizer and 100 mg of Proxel (trade name, manufactured by ICI Co., Ltd.) as a preservative were added to the obtained emulsion. The finally obtained emulsion 1 was a silver iodochlorobromide cubic grain emulsion containing 0.08 mol % of silver iodide and a ratio of silver chlorobromide of 70 mol % of silver chloride and 30 mol % of silver bromide, with an average grain size (equivalent sphere diameter) of 0.22 μm and a coefficient of variation of 9%.
[0136] [Preparation of Photosensitive Layer Coating Solution 1] The above emulsion 1 was mixed with 1,3,3a,7-tetraazaindene (1.2 × 10 -4 mol / mol Ag), hydroquinone (1.2×10 -2 mol / mol Ag), citric acid (3.0×10 -4mol / mol Ag), 2,4-dichloro-6-hydroxy-1,3,5-triazine sodium salt (0.90 g / mol Ag), and further added was latex X1 (trade name "Epocross K-2020E", manufactured by Nippon Shokubai Co., Ltd., a latex of crosslinkable reactive polymer X1 having an oxazoline group as a crosslinkable group) (0.425 g / mol Ag) containing polymer X1 corresponding to the above polymer X, and latex Y1 (described below) (0.425 g / mol Ag) containing polymer Y1 corresponding to the above polymer Y, and then the pH of the solution was adjusted to 5.6 using citric acid to prepare photosensitive layer coating solution 1. The above latex Y1 is a polymer latex containing a polymer Y1 (reactive group: carboxyl group) represented by the following structural formula (P-1), a dispersant consisting of dialkylphenyl PEO sulfate ester, and water (mass ratio of dispersant / polymer: 2.0 / 100=0.02, solid content concentration: 22% by mass).
[0137] [ka]
[0138] [Formation of Undercoat Layer] The above-mentioned latex Y1 was applied to one side of a 40 μm-thick biaxially oriented polyethylene terephthalate (PET) substrate, and dried at 90° C. for 1 minute so that the film thickness after drying was 60 nm, to prepare a substrate with an undercoat layer. The film thickness of the undercoat layer was measured with an electronic micro film thickness meter manufactured by Anritsu Corporation.
[0139] [Process H1, Process A1, Process I1] Next, on the surface of the undercoat layer of the substrate with the undercoat layer, the intermediate layer coating liquid (corresponding to the intermediate layer forming composition) described below, the photosensitive layer coating liquid 1 (corresponding to the photosensitive layer forming composition) and the protective layer coating liquid 1 (corresponding to the protective layer forming composition) described below are simultaneously coated in layers with a coating liquid flow rate ratio (intermediate layer coating liquid / photosensitive layer coating liquid 1 / protective layer coating liquid 1) of 20 / 25 / 10, to form an intermediate layer, a photosensitive layer and a protective layer on the surface of the undercoat layer.This is called film A1.
[0140] (Intermediate layer coating liquid (composition for forming intermediate layer)) The intermediate layer coating liquid is a composition comprising a mixture of latex Y1 and gelatin such that the mass ratio of the weight of polymer Y1 to the weight of gelatin (mass of polymer Y1 / mass of gelatin) is 2 / 1, and further containing a dye that has an optical density of about 1.0 and is decolorized by the alkali of a developer. The intermediate layer coating liquid also contains the above-mentioned latex X1. The content (coating amount) of polymer Y1 in the layer formed from this intermediate layer coating liquid is 0.8 g / m 2 The content (coating amount) of polymer X1 is 0.05 g / m 2 The respective concentrations were adjusted so that the following was satisfied: Since the layer formed from the intermediate layer coating solution contains a dye, the layer has an antihalation function.
[0141] (Protective layer coating solution 1) The protective layer coating solution 1 is a composition containing gelatin. Furthermore, VS-B (K-FJC) (product name: manufactured by FUJIFILM FineChemicals Co., Ltd.) was added as a gelatin crosslinking agent to the protective layer coating solution 1. The content of the gelatin crosslinking agent in the protective layer formed by the protective layer coating solution 1 was 0.022 g / m 2 The amount of the gelatin crosslinking agent added was adjusted so that the gelatin content in the protective layer formed from the protective layer coating solution 1 was 0.08 g / m 2 The concentration of protective layer coating solution 1 was adjusted so as to satisfy the following: The gelatin crosslinking agent is a low molecular weight water-soluble crosslinking agent having the following structure, and is not a polymer type water-insoluble crosslinking agent.
[0142] [ka]
[0143] In the coating film formed on the substrate from the photosensitive layer coating solution 1, the silver content was 6.2 g / m 2 and the content of polymer X1 is 0.01 g / m 2 and the content of polymer Y1 is 0.01 g / m 2 and the gelatin content is 0.62 g / m2 It was.
[0144] [Process B1] Next, the film A1 prepared above was exposed using an exposure machine. A high-pressure mercury lamp was used as the light source, and a mask for forming a lattice pattern as shown in Figure 2 was used as the photomask. In the exposure process, the shape of the photomask and the exposure conditions were set so that the conductive thin lines constituting the square lattice had a line width of 2.5 μm and the length Pa of one side of the lattice (opening) was 300 μm.
[0145] After exposure, the film was developed using a developer described below, and then developed using a fixing solution (product name: N3X-R for CN16X: manufactured by Fujifilm Corporation). After that, the film was rinsed with pure water at 25° C. and dried. The obtained film is referred to as film B.
[0146] The flow of the development process is as follows. [Development Processing Flow] Processing machine: Fujifilm automatic developing machine (FG-710PTS) Processing conditions: Development at 35°C for 30 seconds, Fixation time: 34℃ 23 seconds, Rinse with running water (5L / min) for 20 seconds.
[0147] (Developing Solution Composition) The following compounds are contained in 1 liter (L) of developer: Hydroquinone 0.037mol / L N-Methylaminophenol 0.016mol / L Sodium metaborate 0.140mol / L Sodium hydroxide 0.360mol / L Sodium bromide 0.031mol / L Potassium metabisulfite 0.187mol / L
[0148] [Process C1] Film B was subjected to a heat treatment (superheated steam treatment) by passing film B through a superheated steam bath at 150° C. for 120 seconds. The film after the heat treatment was designated film C.
[0149] [Process D1] Film C was immersed in an aqueous solution of protease (Biophrase AL-15FG, Nagase ChemteX Corporation) (protease concentration: 0.5% by mass, liquid temperature: 40°C) for 120 seconds. Film C was removed from the aqueous solution and immersed in warm water (liquid temperature: 50°C) for 120 seconds and washed. This resulted in Film D (corresponding to a conductive film) that had been subjected to a gelatin decomposition treatment.
[0150] [Process F1] The above film D was subjected to a calendering treatment at a pressure of 30 kN using a calendering device having a combination of a metal roller and a resin roller. The calendering treatment was performed at room temperature.
[0151] [Process G1] The above-mentioned calendered film D was passed through a superheated steam bath at 150° C. for 120 seconds, thereby carrying out a heat treatment (superheated steam treatment) on the calendered film D. The film after the heat treatment is called film E. Film E was a film having a substrate and a metal layer disposed on the substrate and having a mesh pattern made of thin metal wires (line width: 2.5 μm).
[0152] [Process K1] A water dispersion of polyethylenedioxythiophene-polystyrene sulfonate (abbreviation: PEDOT-PSS) (HC Stark, Clevios PH-500 with 5% by mass of dimethyl sulfoxide added; volume resistivity when applied and dried: 1–5×10) was applied to the surface of Film E on which the thin metal wires were formed. -3A resistivity of 1000 Ωcm was applied to the film E. Next, the film E on which the coating film was provided was heated and dried at 120° C. for 20 minutes to form a transparent conductive layer 1. The transparent conductive layer 1 thus formed had a thickness of 200 nm. Finally, the transparent conductive layer 1 was patterned into an electrode pattern shape by a laser ablation method using a laser. This resulted in the production of a conductive film 1 of Example 1, which had a substrate, a metal layer disposed on the substrate and having a mesh pattern made of thin metal wires, and a transparent conductive layer 1 disposed between the thin metal wires on the substrate. In the obtained conductive film 1, the metal layer had a thickness of 1.0 μm, the intermediate layer had a thickness of 0.75 μm, and the protective layer had a thickness of 0.06 μm.
[0153] [Preparation of organic EL element 1] The conductive film 1 was placed in a vacuum deposition chamber, and an organic electroluminescent layer and a cathode were formed by thermal resistance heating deposition on the surface of the transparent conductive layer 1. The structures of the formed organic electroluminescent layer and cathode are shown below. <Anode (transparent conductive layer 1) / Hole injection layer: 2TNATA (4,4',4" tris[2-naphthyl(phenyl)amino]triphenylamine) doped with 0.3 mass% F4-TCNQ (2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane) (300 nm) / Hole transport layer: NPD (naphthyl-substituted diamine derivative) (10 nm) / Emitting layer: CBP (4,4'-N,N'-dicarbazole biphenyl) doped with 5 mass% Ir(ppy)3 (tris(2-phenylpyridine)iridium) / Electron transport layer: BAlq (bis(2-methyl-8-quinolinolato)(p-phenylphenolato)aluminum) (40 nm) / Electron injection layer: LiF (lithium fluoride) (0.5 nm) / Cathode: Al (100 nm)> However, the numbers in parentheses indicate thickness, and the notation " / " means that the two layers before and after it are adjacent to each other. After the organic electroluminescent layer and the cathode were formed, the device was sealed with a sealing plate of a glass substrate using a UV curable adhesive to prepare an organic EL element 1 of Example 1.
[0154] [Fabrication of Solar Cell 1] An aqueous dispersion of polyethylenedioxythiophene-polystyrenesulfonic acid (abbreviation: PEDOT-PSS) (HC Stark, Clevios P AI4083, volume resistivity when coated and dried: 500-5000 Ωcm) was applied to a film thickness of 25 nm on the surface of the transparent conductive layer 1 of the obtained conductive film 1, and the coating was then heated and dried at 120°C for 20 minutes to provide an electron blocking layer. 20 mg of P3HT (poly-3-hexylthiophene, Lisicon SP-001 (trade name), Merck) and PCBM ([6,6]-phenyl C 61 Butanoic acid methyl ester (14 mg, Nanom Spectra E-100H (trade name, manufactured by Frontier Carbon Co., Ltd.) was dissolved in 1 mL of chlorobenzene to prepare a photoelectric conversion layer coating solution. In a glove box substituted with nitrogen, the photoelectric conversion coating solution was spin-coated and dried to form a bulk hetero-type photoelectric conversion layer. The rotation speed of the spin coater was 2000 rpm, and the dry film thickness was 90 nm.
[0155] Lithium fluoride (LiF) was vacuum-deposited on the surface of the bulk hetero layer to a thickness of 1 nm to form an electron-collecting layer. On the surface of the electron collection layer, 2 nm of aluminum and 15 nm of silver were sequentially evaporated to form a multilayered light-transmitting film, which served as the negative electrode. 2 A light-transmitting film was formed using a mask such that: In order to measure the light transmittance of the light-transmitting film, 2 nm of aluminum and 15 nm of silver were sequentially evaporated onto a transparent glass, and the average light transmittance from 400 to 800 nm was determined to be 35%.
[0156] Next, a silicon nitride layer was formed as a protective layer on the surface of the formed negative electrode using a capacitively coupled plasma CVD apparatus. More specifically, the element obtained by forming the negative electrode by the above method was set in a CVD reaction chamber, and then raw material gas according to the following recipe was introduced into the chamber under reduced pressure, and a high frequency power of 13.56 MHz was input to generate plasma, thereby forming a silicon nitride layer. At this time, the film formation time was adjusted so that the thickness of the silicon nitride layer was 2 μm. (Raw material gas recipe) Silane: 25 sccm, ammonia: 15 sccm, hydrogen: 15 sccm, nitrogen: 195 sccm. By the above-mentioned method, a bulk heterotype organic thin-film solar cell 1 of Example 1 was produced.
[0157] [Example 2] (Transparent conductive layer coating liquid 1 (transparent conductive layer forming composition)) Conductive fine particles (manufactured by Ishihara Sangyo Kaisha, Ltd., product name "SN100P") made of tin oxide (SnO2) doped with antimony (Sb) were further added to the protective layer coating solution 1 prepared in Example 1 to prepare a transparent conductive layer coating solution 1. At this time, the content of the conductive fine particles in the transparent conductive layer 2 formed by the transparent conductive layer coating solution 1 was 0.23 g / m 2 The amount of the conductive fine particles added was adjusted so that the transparent conductive layer precursor layer formed by the transparent conductive layer coating solution 1 had the same gelatin and gelatin crosslinking agent contents as those of the protective layer formed by step I1 in Example 1, and the amount of the gelatin crosslinking agent added and the concentration of the coating solution were adjusted.
[0158] A conductive film 2 of Example 2 having a substrate, a metal layer having a mesh pattern made of thin metal wires and disposed on the substrate, and a transparent conductive layer 2 disposed between the thin metal wires on the substrate was produced according to the procedure described in Example 1, except that step J1 described below was performed instead of step I1 and step K1 was not performed. Finally, the transparent conductive layer 2 was patterned into an electrode pattern shape by a laser ablation method using a laser. In step J1, the transparent conductive layer precursor layer 1 was formed according to the procedure described in step I1, except that the transparent conductive layer coating liquid 1 was used instead of the protective layer coating liquid 1. After step J1, step D1 was performed to remove gelatin from the transparent conductive layer precursor layer 1, and a transparent conductive layer 2 was formed.
[0159] Organic EL element 2 of Example 2 was prepared according to the procedure described in [Preparation of organic EL element 1] of Example 1, except that conductive film 2 was used instead of conductive film 1. Moreover, solar cell 2 of Example 2 was produced according to the procedure described in [Production of solar cell 1] of Example 1, except that conductive film 2 was used instead of conductive film 1.
[0160] [Comparative Example 1] [Preparation of Emulsion 2] Emulsion 2 was prepared in the same manner as in Example 1 for emulsion 1, except that the following solution 1 was used, and that after washing and desalting, the emulsion was adjusted to pH 6.4 and pAg 7.5, and then chemical sensitization was not performed. Instead, 100 mg of 1,3,3a,7-tetraazaindene as a stabilizer and 100 mg of Proxel (trade name, manufactured by ICI Co., Ltd.) as a preservative were added to the resulting emulsion. The finally obtained emulsion 2 was a silver iodide-chlorobromide cubic grain emulsion containing 0.08 mol % of silver iodide and a ratio of silver chlorobromide of 70 mol % of silver chloride and 30 mol % of silver bromide, with an average grain size (equivalent sphere diameter) of 0.22 μm and a coefficient of variation of 9%. The physical properties of emulsion 2 were pH=6.4, pAg=7.5, conductivity=4000 μS / cm, and density=1.4×10 3 kg / m 3 , viscosity = 20 mPa·s.
[0161] 1 liquid: 750mL water Gelatin (phthalated gelatin) 20g Sodium chloride 3g 1,3-Dimethylimidazolidine-2-thione 20mg Sodium benzenethiosulfonate 10mg Citric acid 0.7g
[0162] [Preparation of Photosensitive Layer Coating Solution 2] The above-mentioned emulsion 2 was mixed with the following compound (Cpd-1) (8.0×10 -4 mol / mol Ag), and 1,3,3a,7-tetraazaindene (1.2 × 10 -4 The photosensitive layer coating solution 2 was prepared by adding a compound (Cpd-2) below as necessary to adjust the swelling ratio, and then adjusting the pH to 5.6 with citric acid.
[0163] [ka]
[0164] [Process A2] Gelatin was applied to one side of a 40 μm-thick biaxially oriented polyethylene terephthalate (PET) substrate, and dried at 90° C. for 1 minute so that the dried film thickness was 60 nm, to prepare a substrate with a gelatin undercoat layer. Next, the above-mentioned photosensitive layer coating solution 2 was applied onto the surface of the gelatin undercoat layer of the substrate with the gelatin undercoat layer to form a photosensitive layer 2. In the photosensitive layer formed using the photosensitive layer coating solution 2, the silver / binder volume ratio was 1.03 / 1 and the silver content was 8.0 g / m 2 and the gelatin content is 0.99 g / m 2 It was.
[0165] [Process I2] The following protective layer coating solution 2 was then applied to the surface of the photosensitive layer 2 formed using the photosensitive layer coating solution 2, and the coating film was then dried to produce a film A3 having the photosensitive layer 2 and the protective layer 2, in that order, on the surface of the undercoat layer.
[0166] (Protective layer coating solution 2) Protective layer coating solution 2 was prepared by mixing the following components. Water 943mL 10g gelatin A surfactant, a preservative, and a pH adjuster were appropriately added to the protective layer coating solution 2. The gelatin content in the protective layer 2 formed by the protective layer coating solution 2 was 0.05 g / m 2 It was.
[0167] A conductive film 3 of Comparative Example 1 having a substrate, a metal layer having a mesh pattern made of thin metal wires disposed on the substrate, and a transparent conductive layer 1 disposed between the thin metal wires on the substrate was produced according to the procedure described in Example 1, except that the above-mentioned film A3 was used instead of the film A1 in step B1. Finally, the transparent conductive layer 1 was patterned into an electrode pattern shape by a laser ablation method using a laser.
[0168] Organic EL element 3 of Comparative Example 1 was prepared according to the procedure described in [Preparation of Organic EL element 1] of Example 1, except that conductive film 3 was used instead of conductive film 1. Moreover, solar cell 3 of Comparative Example 1 was produced according to the procedure described in [Production of solar cell 1] of Example 1, except that conductive film 3 was used instead of conductive film 1.
[0169] [Comparative Example 2] (Transparent conductive layer coating liquid 2) Transparent conductive layer coating solution 2 was prepared by mixing the following components. Water 943mL 10g gelatin Conductive particles made of Sb-doped tin oxide: 48.4g (Manufactured by Ishihara Sangyo Kaisha, product name "SN100P") To the transparent conductive layer coating solution 2, a surfactant, a preservative, and a pH adjuster were added as appropriate.
[0170] Following the same procedure as in Comparative Example 1, photosensitive layer coating solution 2 was applied onto the surface of the gelatin undercoat layer of the substrate with the gelatin undercoat layer to form photosensitive layer 2. Next, a transparent conductive layer 3 was formed according to the procedure of step I2 of Comparative Example 1, except that the above transparent conductive layer coating solution 2 was used instead of the protective layer coating solution 2, to produce a film A4 having a photosensitive layer 2 and a transparent conductive layer 3 in this order on the surface of the undercoat layer. Note that the content of the conductive fine particles in the formed transparent conductive layer 3 was 0.23 g / m 2 and the gelatin content is 0.05 g / m 2 It was.
[0171] A conductive film 4 of Comparative Example 2 having a substrate, a metal layer having a mesh pattern made of thin metal wires disposed on the substrate, and a transparent conductive layer 3 disposed between the thin metal wires on the substrate was produced according to the procedure described in Example 1, except that in step B1, the above-mentioned film A4 was used instead of the film A1, and step K1 was not performed. Finally, the transparent conductive layer 3 was patterned into an electrode pattern shape by a laser ablation method using a laser.
[0172] Organic EL element 4 of Comparative Example 2 was prepared according to the procedure described in [Preparation of Organic EL element 1] of Example 1, except that conductive film 4 was used instead of conductive film 1. Moreover, solar cell 4 of Comparative Example 2 was produced according to the procedure described in [Production of solar cell 1] of Example 1, except that conductive film 4 was used instead of conductive film 1.
[0173] [Measurement and Evaluation] [Measurement of gelatin content in thin metal wire] The gelatin content in the thin metal wires of each of the conductive films produced in the Examples and Comparative Examples was measured by the following BCA method (bicinchoninic acid method). More specifically, the conductive film 1 of Example 1 was cut in the thickness direction, and only the region in which the thin metal wires constituting the mesh pattern were arranged was taken out to obtain a sample for measuring the gelatin content. A reducing liquid ("FR-1" manufactured by Fujifilm Corporation, containing cerium sulfate) and ion-exchanged water were mixed in a volume ratio of 1:2 to prepare a desilvering liquid. The obtained desilvering liquid was kept at 25°C, and the above sample was immersed in it for 10 minutes while stirring with nitrogen. Next, the sample was immersed in ion-exchanged water for 2 seconds, washed thoroughly with water for 15 minutes, and dried at room temperature to obtain a desilvering sample. The area of the region in which the thin metal wires were arranged was measured to obtain a gelatin content measurement sample of 1 cm2. 2 A desilvered sample equivalent to the amount of gelatin was placed in a test tube, 2.5 mL of ion-exchanged water was added, and the mixture was mixed to prepare a sample for gelatin quantification.
[0174] A gelatin solution for a calibration curve was prepared by mixing 10 g of gelatin with 115 g of ion-exchanged water, swelling for 30 minutes, and then dissolving with stirring at 40°C for 30 minutes. Gelatin solutions for a calibration curve with different gelatin contents were also prepared in the same manner as above, except that 5 g of gelatin was mixed with 120 g of ion-exchanged water, 5 g of gelatin with 245 g of ion-exchanged water, and 5 g of gelatin with 495 g of ion-exchanged water. 2.5 mL of each gelatin solution for a calibration curve was placed in a test tube.
[0175] Reagent A, Reagent B, and Reagent C from the Micro BCA Protein Assay Kit (Thermo Scientific) were mixed in a volume ratio of 25:24:1 to prepare a quantitative reagent. 2.5 mL of the above quantitative reagent was added to each test tube containing the gelatin solution for the calibration curve and the sample for gelatin quantification, then the tubes were sealed and thoroughly stirred. All samples were shaken in a thermostatic shaker at 60°C for 1 hour at a shaking speed of 160 reciprocations / min. After cooling the shaken samples to room temperature for 10 minutes, the absorbance of each sample at 562 nm was immediately measured using a spectrophotometer (Hitachi, Ltd. "U-3300"). The gelatin content in the sample for gelatin quantification was calculated by comparing the absorbance of the sample for gelatin quantification with the absorbance of the gelatin solution for the calibration curve, and the gelatin content in the thin metal wire was measured. Table 1 below shows the measured gelatin content in the thin metal wires in the conductive films of each of the Examples and Comparative Examples, measured by the above-mentioned method.
[0176] [Measurement of sheet resistance value] The sheet resistance of the transparent conductive layer was measured for each conductive film produced in the examples and comparative examples. The sheet resistance was measured using a resistance measuring device "Loresta-GXII MCP-T710" (manufactured by Nitto Seiko Analytech Co., Ltd.). The measured sheet resistance value of the conductive film of each example is shown in Table 1 described later.
[0177] [Evaluation of Organic EL Devices] A voltage was applied to the organic EL elements produced in each of the Examples and Comparative Examples, the luminance-current-voltage characteristics of each organic EL element were measured, and the luminous efficiency (unit: cd / A) was calculated. In addition, the organic EL elements manufactured in each Example and Comparative Example were left for 2 days in an environment of 20°C and 40% RH, and then a voltage of 10V was applied to each organic EL element to cause it to emit light, and the state of the light-emitting region of the organic EL element was observed. From the observation results of each organic EL element, the ratio (non-light-emitting rate) (%) of the area occupied by the area of the effective light-emitting region where no light was observed (non-light-emitting region) to the total area of the area of the light-emitting layer that can be observed from the normal direction of the organic EL element (effective light-emitting region) was calculated. Note that the area that was shielded by metal wiring was excluded from the effective light-emitting region. The measured luminous efficiency of the organic EL device of each example and the non-luminous rate after being left for two days are shown in Table 1 described later.
[0178] [Evaluation of solar cells] The solar cells immediately after fabrication in each example were measured at 25°C, 10% relative humidity, and AM1.5G, 100mW / cm using a Pexel Technologies L12 solar simulator. 2While irradiating the solar cells with simulated sunlight, the current was measured using a source measure unit (SMU2400 type, manufactured by KEITHLEY) in the voltage range of -0.1 V to 1.0 V. The obtained current-voltage characteristics were evaluated using an IV curve analyzer manufactured by Pexel Technologies, and the conversion efficiency of each solar cell was calculated.
[0179] Next, the solar cells fabricated in each example were left to stand in a nitrogen atmosphere with a dew point of -60°C for 200 hours, and then, in the same manner as above, were subjected to AM1.5G, 100mW / cm 2 The solar cells were irradiated with simulated sunlight and the current values were measured, and the conversion efficiency of each solar cell was calculated from the evaluation results of the current-voltage characteristics. The retention rate of the conversion efficiency was calculated based on the following formula from the results of measuring the conversion efficiency immediately after fabrication and after the aging test. The measurement results are shown in Table 1. Conversion efficiency retention rate (%) = (conversion efficiency after aging test) ÷ (conversion efficiency immediately after production) × 100
[0180] Table 1 below shows the materials constituting each layer of the conductive film produced in each Example or Comparative Example, the sheet resistance of the conductive film, and the evaluation results for the organic EL device and solar cell. In the table, the column "undercoat layer" indicates the components constituting the undercoat layer of each conductive film. In the table, the "polymer component" column for "metal layer" indicates the polymer contained in the metal layer of each conductive film. In the table, the column "Transparent conductive layer" indicates the components contained in the transparent conductive layer of each conductive film.
[0181] [Table 1]
[0182] As shown in Table 1, it was confirmed that the conductive film of the present invention can provide the desired effects. This demonstrates that the conductive film of the present invention is suitable as a transparent electrode for flexible solar cells and flexible organic EL elements. [Explanation of symbols]
[0183] 10 Conductive film 12 Substrate 12a surface 14 Metal layer 16 Fine metal wire 18 Transparent conductive layer 20 Opening
Claims
1. A substrate; A metal layer composed of thin metal wires arranged on the substrate; A conductive film having a transparent conductive layer disposed between the thin metal wires on the substrate, the thin metal wire contains metal particles and a polymer compound different from gelatin, The thin metal wire does not contain gelatin, or, if the thin metal wire contains gelatin, the gelatin content in the thin metal wire is 0.100 g / m 2 The conductive film is as follows:
2. The conductive film according to claim 1 , wherein the polymer compound contains a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer.
3. The conductive film of claim 1 , wherein the transparent conductive layer comprises fine particles of a conductive metal oxide and a binder.
4. The conductive film according to claim 3 , wherein the binder is a resin containing a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer.
5. The conductive film of claim 3 , wherein the conductive metal oxide is antimony doped tin oxide.
6. The conductive film of claim 1 , wherein the transparent conductive layer comprises a conductive polymer.
7. The conductive film of claim 6 , wherein the conductive polymer comprises polyethylenedioxythiophene with polystyrenesulfonic acid as a counterion.
8. a primer layer disposed between the substrate and the metal layer; the undercoat layer contains a resin including a repeating unit derived from a styrene-based monomer and a repeating unit derived from a (meth)acrylate-based monomer; The conductive film according to claim 1 .
9. 2. The conductive film according to claim 1, wherein the thin metal wires have a line width of 1 to 4 μm.
10. The conductive film according to claim 1 , further comprising a mesh pattern formed by the thin metal wires.
11. The conductive film according to claim 10 , wherein the mesh pattern has a rhombus shape.
12. The conductive film according to claim 1, wherein the substrate has a thickness of 30 to 50 μm.
13. The conductive film according to claim 1 , wherein the transparent conductive layer is disposed in a pattern.
14. A solar cell comprising the conductive film according to any one of claims 1 to 13.
15. An organic electroluminescence device comprising the conductive film according to any one of claims 1 to 13.
Citation Information
Patent Citations
Conductive element and method of manufacturing the same, and photosensitive material for forming the same
JP2011138628A